Phytochemical compounds and antioxidant capacities of Abelmoschus manihot leaf extracts using different solvents - GRACE MARLINA WINATA; HARDINSYAH HARDINSYAH; SRI ANNA MARLIYATI; RIMBAWAN RIMBAWAN; DIMAS ANDRIANTO (Society for Indonesian Biodiversity, 2024)
Abstract. Winata GM, Hardinsyah H, Marliyati SA, Rimbawan R, Andrianto D. 2024. Phytochemical compounds and antioxidant capacities of Abelmoschus manihot leaf extracts using different solvents. Biodiversitas 25: 942-949. Gedi (Abelmoschus manihot (L.) Medik) leaves are popularly consumed as a green vegetable by Eastern Indonesians. This work aimed to carry out the phytochemical compounds and antioxidant capacities of five extracts, i.e., water, 70% ethanol, absolute ethanol, ethyl acetate, and hexane of Abelmoschus manihot leaf. Qualitative analysis was done as a preliminary screening for flavonoid, tannin, saponin, alkaloid, triterpenoid, steroid, and quinone. Quantitative analysis determined the flavonoid, phenolic, tannin, quercetin, and steroid content. In-vitro antioxidant analysis was conducted to determine free radical scavenging activity and lipid peroxidation inhibitory activity. The results showed that flavonoid was only found in 70% ethanol extract; steroid was obtained in all extracts, while alkaloid, saponin, tannin, quinone, and triterpenoid were absent in all extracts. The results of the quantitative analysis showed that the highest flavonoid was in 70% ethanol extract (39.2 mg GAE/g), phenolic in ethyl acetate extract (34.792 mg QE/g), tannin in 70% ethanol (1.395 mg/g), quercetin in absolute ethanol extract (0.246 mg/g), and steroid content in hexane extract (201.948 mg/g). Half maximal inhibitory concentration (IC50) of each extract to inhibit malondialdehyde (MDA) formation was lower than free radical scavenging activity. The IC50 values of MDA formation in absolute ethanol and hexane extracts were 6.77 ppm and 7.67 ppm, respectively. The IC50 of vitamin E was 3.67 ppm. Further study is needed to determine the mechanism of Abelmoschus manihot leaf extracts as antioxidants used as a functional food.